The rainy day - Milbourne, Anna.; Parker, Laura; Fearn, Laura; Gill, Sarah (Tulsa, OK : EDC Pub., 2005)
Explains how and why rain happens.
Mode of access: Internet.
Keywords: Rain and rainfall -- Pictorial works; Rain and rainfall -- Pictorial works -- Juvenile literature